Studi Deskriptif Subjective Well-Being Remaja Panti Asuhan di Masa Covid-19 - Aghnia Nafilah Nur Annisa; Ihsana Sabriani Borualogo (Bandung Conference Series: Psychology Science, 2022)
Abstract. Indonesia has implemented Pembatasan Sosial Berskala Besar (PSBB) to prevent the spread of COVID-19. COVID-19 does not only have an impact on the individual's physical but psychological as well. Where COVID-19 has affected the mental health of adolescents living in orphanages. The study has shown the increasing concern felt by the orphanage adolescents age 10 to 18 during the COVID-19 period. This affects their subjective well-being (SWB). This study aims to determine how the SWB for adolescents at the orphanage in the city of Bandung also includes the concerns on how they feels during the COVID-19 period. Participants involved this study are (N = 380; 43.2% male and 56.8% female). The sampling technique used is cluster random sampling. The measuring instruments used in this study were from Children's World, namely CW-SWBS5, Children World Under COVID-19 and CW-PNAS. The results of this study showed that younger male adolescents (M = 83.55; SD = 16.81) had higher SWB scores than female adolescents (M = 78.53; SD = 20.28) who were older. Overall, the orphanage adolescents had a mean SWB score (M = 80.70; SD = 19.00). According to the Cummins homeostasis theory, this score is above the normal average SWB score, which means that orphanage adolescents feel well-being during the COVID-19 period. Meanwhile, male worries were higher than females, and as they got older, their worries decreased. Orphanage adolescents reported increase stress and boredom with age, as well as a decreased pleasure and excitement during the COVID-19 period. Boredom and loneliness were also higher in female adolescents than male adolescent. Abstrak. Indonesia melakukan penerapan Pembatasan Sosial Berskala Besar (PSBB) untuk mencegah penyebaran COVID-19. COVID-19 tidak hanya berdampak pada fisik individu namun psikologis juga. Dimana COVID-19 telah mempengaruhi kesehatan mental remaja yang tinggal di Panti Asuhan. Yang ditunjukan dengan adanya peningkatan kekhawatiran yang dirasakan remaja Panti Asuhan usia 8-10 tahun selama masa COVID-19. Hal tersebut mempengaruhi subjective well-being (SWB) mereka. Penelitian ini bertujuan untuk mengetahui bagaimana SWB remaja Panti Asuhan di Kota Bandung yang juga meliputi kekhawatiran yang mereka rasakan pada masa COVID-19. Partisipan penelitian ini (N = 380; 43.2% laki-laki dan 56.8% perempuan). Teknik sampling yang digunakan yaitu cluster random sampling. Alat ukur yang digunakan pada penelitian ini dari Children’s World yaitu CW-SWBS5, Children World Under COVID-19 dan CW-PNAS. Hasil penelitian ini menunjukan remaja laki-laki (M = 83.55; SD = 16.81) dengan usia lebih muda memiliki skor SWB lebih tinggi dibandingkan remaja perempuan (M = 78.53; SD = 20.28) dengan usia lebih tua. Secara keseluruhan remaja panti asuhan memiliki skor means SWB (M = 80.70; SD = 19.00). Menurut teori homeostasis Cummins skor tersebut berada di atas rata-rata normal skor SWB yang artinya remaja panti asuhan merasa well-being di masa COVID-19. Sedangkan pada kekhawatiran laki-laki memiliki kekhawatiran lebih tinggi dibandingkan perempuan dan seiring bertambahnya usia kekhawatiran mereka menurun. Remaja panti asuhan melaporkan seiring bertambahnya usia adanya peningkatan pada stres dan bosan juga penurunan pada kesenangan dan semangat selama masa COVID-19. Kebosanan dan kesepian juga lebih tinggi pada remaja perempuan dibandingkan remaja laki-laki.